Open classroom organization and implementation: A Case Study of “Introduction to Radio Frequency Identification and Internet of Things” - Qiang Li (SHS Web of Conferences)
Introduction to Radio Frequency Identification and Internet of Things is an elective course offered to all students in the school, so student’s major are relatively complex; the course belongs to interdisciplinary fields, which results in a relatively large teaching content for this course. The traditional teaching mode cannot cover the knowledge points of the subject within 32 class hours, nor can it meet the learning needs of students from different majors. Therefore, it is necessary to change the existing teaching methods to meet the needs of course implementation. Open classroom is a course organization model in which teachers use methods such as collaborative exploration, cooperative learning, and heuristic teaching in the classroom. The classroom has high knowledge density, flexible teaching methods, and encourages knowledge exchange between students and between teachers and students. It is particularly suitable for the interdisciplinary technical characteristics and the course characteristics of elective courses. Teaching practice has proven that after adopting open classrooms in this course, students’ learning enthusiasm and knowledge perspectives have greatly improved.